A qualitative study of the impact of peer support on women's mental health treatment experiences during the perinatal period - Chloe Rice; Emma Ingram; Heather O'Mahen (BMC, 2022)
Abstract Background Perinatal mental health problems are prevalent, affecting up to 20% of women However, only 17-25% receive formal support during the perinatal period. In this qualitative study, we sought to examine women's experiences with peer support for mental health problems during the perinatal period. Methods Semi-structured interviews and focus groups were conducted with twenty-five mothers from the UK who had utilised peer support for a perinatal mental health problem. Data was analysed using thematic analysis. Results Seven major themes were identified in women's help seeking process and experience of peer support. These included; perinatal specific precipitating factors that contributed to their mental health problems, barriers in the form of unhelpful professional responses, feelings of isolation, acceptance of the problem and need to actively re-seek support, finding support either through luck or peer assistance. Conclusion Peer support showed promise as an effective means to reduce perinatal mental health difficulties; either as a form of formal support or as an adjunct to formal support. The results highlight ways to improve perinatal women's access to mental health support through peer-based mechanisms.